Absorption Kinetics and Subcellular Fractionation of Zinc in Winter Wheat in Response to Nitrogen Supply - Nie, Zhaojun; Zhao, Peng; Wang, Jia; Li, Jinfeng; Liu, Hongen (Frontiers in Plant Science, 2017)
Nitrogen (N) is critical for zinc (Zn) absorption into plant roots; this in turn allows for Zn accumulation and biofortification of grain in winter wheat (Triticum aestivum L.), an important food crop. However, little is known about root morphology andsubcellular Zn distribution in response to N treatment at different levels of Zn supply. In this study, two nutrient solution culture experiments were conducted to examine Zn accumulation, Zn absorption kinetics, root morphology, and Zn subcellular distribution in wheat seedlings pre-cultured with different N concentrations. The results showed positive correlations between N and Zn concentrations, and N and Zn accumulation, respectively. The findings suggested that an increase in N supply enhanced root absorption and the root-to-shoot transport of Zn. Nitrogen combined with the high Zn (Zn10) treatment increased the Zn concentration and consequently its accumulation in both shoots and roots. The maximum influx rate (Vmax), root length, surface area, and volume of 14-d-old seedlings, and root growth from 7 d to 14 d in the medium N (N7.5) treatment were higher, but the Michaelis constant (Km) and minimum equilibrium concentrations (Cmin) in this treatment were lower than those in the low (N0.05) and high (N15) N treatments, when Zn was supplied at a high level (Zn10). Meanwhile, there were no pronounced differences in the above root traits between the N0.05Zn0 and N7.5Zn10 treatments. An increase in N supply decreased Zn in cell walls and cell organelles, while it increased Zn in the root soluble fraction. In leaves, an increase in N supply significantly decreased Zn in cell walls and the soluble fraction, while it increased Zn in cell organelles under Zn deficiency, but increased Zn distribution in the soluble fraction under medium and high Zn treatments. Therefore, a combination of medium N and high Zn treatments enhanced Zn absorption, apparently by enhancing Zn membrane transport and stimulating root development in winter wheat. An increase in N supply was beneficial in terms of achieving a balanced distribution of Zn subcellular fractions, thus enhancing Zn translocation to shoots, while maintaining normal metabolism.